1986
DOI: 10.2739/kurumemedj.33.21
|View full text |Cite
|
Sign up to set email alerts
|

An experimental study of gastric mucosal proliferation due to regurgitation of duodenal contents.

Abstract: Summary: The changes in morphology and cell proliferation of the gastric mucosa were studied with in vivo experiments on several models of duodenal regurgitation.The following operations were performed on six groups (A-F) of male Wistar rats : (A) sham operation, (B) gastro-je junostomy without gastrectomy, (C) gastrectomy with Billroth II reconstruction, (D) gastrectomy with Billroth I reconstruction, (E) gastrectomy with Billroth II reconstruction and Braun's anastomosis, and (F) gastrectomy and Roux-Y gastr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

1989
1989
1991
1991

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 21 publications
0
1
0
Order By: Relevance
“…Most authors report a median patient age of 60-70 years at the time of in the residual stomach. Kobukata (1986) reported that the conditions responsible for the duodeno -gastric ref lux precede an increase in cell proliferation, which in turn may be one of the most important factors for carcinogenesis in the residual stomach following gastrectomy.…”
Section: Discussionmentioning
confidence: 99%
“…Most authors report a median patient age of 60-70 years at the time of in the residual stomach. Kobukata (1986) reported that the conditions responsible for the duodeno -gastric ref lux precede an increase in cell proliferation, which in turn may be one of the most important factors for carcinogenesis in the residual stomach following gastrectomy.…”
Section: Discussionmentioning
confidence: 99%